2020
DOI: 10.7759/cureus.7950
|View full text |Cite
|
Sign up to set email alerts
|

Gallbladder Tuberculosis Mimicking Gallbladder Carcinoma: A Case Report and Review of the Literature

Abstract: Gallbladder tuberculosis (GT) is an extremely rare disease entity, even in our country Morocco known for being an endemic area. The lack of pathognomonic clinical presentation and radiological features of GT makes preoperative diagnosis unlikely and poses a diagnostic dilemma regarding gallbladder carcinoma (GC). The diagnosis is usually made by histological examination after cholecystectomy, highlighting the importance of sending every gallbladder specimen to pathology. We report an exceedingly rare case of G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Mycobacterium tuberculosis (MTB) commonly affects the lungs and solitary TB of the gallbladder is one of the rarest sites of extrapulmonary TB infection. The reason the gallbladder is less susceptible to infection is related to the highly alkaline environment of bile and the inhibitory effect on MTB of the bile acids [1][2]. The pathogenesis of gallbladder TB is unknown, and the route of infection is mostly considered to be caused by hematogenous or lymphatic spreading.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mycobacterium tuberculosis (MTB) commonly affects the lungs and solitary TB of the gallbladder is one of the rarest sites of extrapulmonary TB infection. The reason the gallbladder is less susceptible to infection is related to the highly alkaline environment of bile and the inhibitory effect on MTB of the bile acids [1][2]. The pathogenesis of gallbladder TB is unknown, and the route of infection is mostly considered to be caused by hematogenous or lymphatic spreading.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of gallbladder TB is unknown, and the route of infection is mostly considered to be caused by hematogenous or lymphatic spreading. Cholelithiasis and biliary obstruction are considered the most important factors in the development of gallbladder TB [2][3][4]. The clinical manifestations of gallbladder TB are not typical, with most patients presenting chronic cholecystitis with right upper quadrant pain or gallbladder mass.…”
Section: Discussionmentioning
confidence: 99%
“…Rarely, multi-cystic form has been described. A recent review found only about 120 cases reported in world literature to date [5]. The differential diagnosis includes gallbladder malignancy or xantho-granulomatous cholecystitis.…”
Section: Gallbladder Tuberculosismentioning
confidence: 99%
“…There have been few cases of gallbladder TB recorded in the literature, making it an uncommon condition [2]. The most common clinical signs and symptoms are fever, anemia, anorexia, weight loss, and abdominal discomfort [3]. Gallstones, wall thickening, or a mass may be detected in the gallbladder with ultrasonography.…”
mentioning
confidence: 99%